Sejren der ikke blev vundet: Pseudonymet Anti-diabolos’ kamp mod forsagelsen og trosbekendelsen i dåbspagten - Petersen, Carsten Elmelund (Kirkehistoriske Samlinger, 2024)
This article studies an 1867 publication on baptism, published under the pseudonym Anti-diabolos. The author was the lay theologian Christian Møller. Møller’s understanding of baptism, developed in Anti-diabolos’ writing and elsewhere, is intricately linked to his understanding of the baptismal covenant. Notably, despite distancing himself from the Baptist view, Møller aligns with Baptists in emphasizing regeneration through the Word. Møller’s critique met opposition from other Revialist authors. His rejection of the baptismal covenant and associated rituals drew further scrutiny, especially regarding his alignment with Rosenius, who emphasized the covenantal aspect of baptism as both a separation from sin and a promise of salvation. Møller’s pseudonymous critique inadvertently revealed contradictions in his earlier writings, where he had supported the conditional nature of the baptismal covenant. His theological evolution led to a break with Pastor Trandberg’s free congregation on the island of Bornholm in 1866 and his return to the Danish National Church, culminating in the formation of the Lutheran Mission Society in 1868. Despite initial sharp polemics, Moller later moderated his stance, evident in an 1884 book on baptism, where he emphasized grace as unmerited and unconditional while still affirming baptism as a means of regeneration. Moller’s evolving theology on baptism, from polemical attacks on the baptismal covenant to a more balanced Lutheran perspective, reflects his journey through theological crises and engagement with broader revivalist debates. His writings reveal the complexities and tensions in navigating between legalistic and evangelical understandings of baptism and grace.